Alginate-embedded HuH-7 cells increase MMP-9 and reduce OCLN expression in vitro. Issue 1 (December 2017) - Angiolini, Virginia; Cruz, Carolina; López, Mónica; Simon, Laura; Matte, Ursula
Abstract Background Hepatocellular carcinoma is a common cancer, ranking third in cancer-associated deaths. An important cause of cancer patients' mortality is metastasis. At the start of metastasis progression, there is an epithelial-mesenchymal transition, characterized by matrix degradation, junction reductions and vessels formation. HuH-7 is a cell line used in research as an in vitro model for hepatocellular carcinoma. It is known that two-dimensional growth reflects tumor characteristics poorly. In contrast, three-dimensional cultures provide a better approach to the study of tumorigenic potential. The purpose of this work was to mimic a three-dimensional environment in order to assess gene expression of some epithelial-mesenchymal transition and metastasis progression markers in HuH-7 cells and compare them with traditional two-dimensional culture model. Methods HuH-7 cells were encapsulated in sodium alginate (three-dimensional model) to be compared with cells grown in two-dimensional flasks. After 4 days in culture, gene expression ofMatrix metallopeptidase 9, Occludin, p65, Intercellular adhesion molecule 1 andVascular endothelial growth factor A was analyzed byq PCR and cytoskeleton assessment was performed by rhodamine-phalloidin staining. Results Differences were found in gene expression, with a high increment ofMatrix metallopeptidase 9 andOccludin reduction. The cytoskeleton morphology also showed differences, with a cytoplasm restricted only near the nuclei in the three-dimensional model. Conclusions This work shows the effects of using sodium alginate capsules as a three-dimensional model to the study of HuH-7. Cells in this 3D system show key markers of epithelial-mesenchymal transition, such asMatrix metallopeptidase 9 overexpression andOccludin down-regulation.